Longitudinal comparison of young swimmers' anthropometrics, hydrodynamics, kinematics and efficiency by cluster analysis - Morais, J. E.; Forte, P.; Costa, M. J.; Marinho, D. A.; Silva, A. J.; Barbosa, T. M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of this study was to identify the variables that better discriminate young swimmers` biomechanical profile during a competitive season by a cluster analysis. Fifteen boys and eighteen girls were evaluated three times throughout a competitive season. Arm span, chest perimeter, stroke length, velocity, speed fluctuation, coefficient of active drag, propelling efficiency and stroke index were selected as variables. Cluster and discriminant analysis were computed, and MANOVA used to verify the gender and performance effects. Swimmers` classification is mainly determined by anthropometric, kinematic/efficiency and hydrodynamic features. Throughout the season the changes in the clustering solution suggests moderate-high stability in their biomechanical profile.